Relationship Between Satisfaction and Employee Performance at Scholoo Keyen Hospital in 2024 - Yuliana Yulce Howay; Nilawati Uly; Achmad R. Muttaqien Al-Maidin; Zamli Zamli (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Human resources (HRM), as the main organ of an organization, plays a critical role in achieving the organization's goals. The degree of patient satisfaction is influenced by how the hospital serves them. Objective: The goal of this study is to determine the relationship between staff satisfaction and performance at the Scholoo Keyen District General Hospital in Sorong South District. Method: Researchers gather data from a group of respondents using a type of survey research, a quantitative research method, to try to understand how a particular phenomenon can occur. Result: The results of research based on performance variables show that the performance category is less than 0 people (0%), adequate is 11 people (8,3%), and the good category is 121 people (91,7%). The satisfaction variable shows the category of less than 0 people (0%), 34 people (25,8%) in the fair category, and 98 people (74,2%) in the good category. The Kruskall-Wallis test results show variable satisfaction with employee performance, with a p-value of 0,000. Conclusion: According to the Kruskal-Wallis test, the p-value for satisfaction with employee performance was 0.000. p-valued 0,000 < 0,05 until Ho rejected If accepted, we can assert a relationship between employee satisfaction and performance in the RSUD Scholoo Keyen district of Sorong South.